Blood on the tracks - Nickless, Barbara (Thomas & Mercer, 2016)
"A young woman is found brutally murdered, and the main suspect is the victim's fiancé, a hideously scarred Iraq War vet known as the Burned Man. But railroad police Special Agent Sydney Rose Parnell, brought in by the Denver Major Crimes unit to help investigate, can't shake the feeling that large forces are behind this apparent crime of passion. In the depths of an icy winter, Parnell and her K9 partner, Clyde--both haunted by their time in Iraq--descend into the underground world of a savage gang of rail riders. There, they uncover a wide-reaching conspiracy and a series of shocking crimes. Crimes that threaten everything Parnell holds dear. As the search for the truth puts her directly in the path of the killer, Parnell must struggle with a deadly question: Can she fight monsters without becoming one herself?"--Back cover.